COMMUNICATION OF THE CHILDREN WITH AUTISM IN SLBN SURAKARTA: GRICE’S COOPERATIVE PRINCIPLES - Dian Wahyunianto; Djatmika Djatmika; Dwi Purnanto (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2019)
Autism is also believed to be one of the linguistics impairment causes. Not only having problems in the language acquisition in general, but pragmatic deficit has also become serious problem of the children with autism. The objective of this study is to demonstrate how children with autism obey the Grice’s cooperative principles. There are 5 children with autism that become subjects of this study. Those 5 children are specifically children with autism that is categorized as verbal autism children. The data are speech produced by the children with autism in the class. Data collection is done by recording and followed by transcribing. It is analyzed using Grice’s cooperative principles with 4 maxims to be obeyed. The results showed that most of the utterances produced by the children with autism obeying 2 maxims with the most frequent maxim to be obeyed was maxim of quantity.